Causal relationship between green tea intake and gastrointestinal disorders: a two-sample Mendelian randomization study - Chen, Chan; Lin, Yifei; Xu, Jinni; Chen, Qingquan; Huang, Jing (Frontiers in Nutrition, 2024)
The precise association between green tea intake and gastrointestinal disorders remains controversial. This study aimed to investigate the potential causal association bewteen green tea intake and gastrointestinal disorders through a two-sample Mendelian randomization (MR) study. Methods: Utilizing publicly accessible data from genome-wide association studies (GWAS), we identified SNPs strongly linked with the study variables from multiple large databases to serve as instrumental variables (IVs). MR analyses were executed utilizing the inverse variance weighting (IVW) method, with the resultant effect estimates serving as the primary outcome measure. In addition, a multivariate MR design was performed to adjust for smoking and alcohol consumption. To ensure the robustness of our findings, a series of sensitivity analyses were conducted to assess reliability. Results:Univariable MR analysis revealed suggestive associations between green tea intake and gastroesophageal reflux (OR = 0.9950, 95%CI 0.9900-1.0000, PIVW = 0.047), diverticulosis (OR = 0.9998, 95%CI 0.9996-1.0000, PIVW = 0.030), Crohn's disease (OR = 1.0001, 95%CI 1.0000-1.0002, PIVW = 0.019), and cholangitis was observed(OR = 1.0440, 95%CI 1.0100-1.0790, PIVW = 0.011). Multivariate MR analysis indicated after controlling for potential confounders, greater green tea consumption was suggestively associated with the decreased risk of oesophagitis (OR = 0.9667, 95% Cl: 0.9405-0.9936, PIVW = 0.016) and gastric cancer (OR = 0.9810, 95% Cl: 0.9628-0.9996, PIVW = 0.046). Nevertheless, multivariate MR analysis also showed that greater green tea consumption was suggestively associated with the increased risk of Crohn's disease (OR = 1.0001, 95% Cl: 1.0000-1.0002, PIVW = 0.007). Sensitivity analyses confirmed that these results were reliable.Our study provides suggestive evidence that genetically predicted green tea intake is causally associated with the risk of oesophagitis, gastric cancer and Crohn's disease, but a larger GWAS database is needed for validation.